1997
DOI: 10.1002/(sici)1097-0177(199711)210:3<249::aid-aja6>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte survival and differentiation in situ are integrin mediated

Abstract: Chondrocytes in specific areas of the chick sternum have different developmental fates. Cephalic chondrocytes become hypertrophic and secrete type X collagen into the extracellular matrix prior to bone deposition. Middle and caudal chondrocytes remain cartilaginous throughout development and continue to secrete collagen types II, IX, and XI. The interaction of integrin receptors with extracellular matrix molecules has been shown to affect cytoskeleton organization, proliferation, differentiation, and gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 10 publications
(14 reference statements)
4
29
0
Order By: Relevance
“…Disruption with cytochalasin D blocked BMP 7-mediated increase in type II collagen expression (Vinall et al, 2002). Moreover, actin cytoskeleton disruption by treatment with an anti-beta1 integrin antibody inhibited type X collagen deposition (Hirsch et al, 1997). In our study, cytochalasin D blocked the redifferentiation of chondrocytes on chitosan membrane (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Disruption with cytochalasin D blocked BMP 7-mediated increase in type II collagen expression (Vinall et al, 2002). Moreover, actin cytoskeleton disruption by treatment with an anti-beta1 integrin antibody inhibited type X collagen deposition (Hirsch et al, 1997). In our study, cytochalasin D blocked the redifferentiation of chondrocytes on chitosan membrane (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…This suggestion is in accordance with several experimental evidences considering cell-matrix interactions as a basic process influencing chondrocyte differentiation. In this way, it has been reported that chondrocyte survival and differentiation is highly dependent on the interaction of cells with extracellular matrix molecules via integrins (37) and that exposition of early hypertrophic chondrocytes to a specific microenviroment composed of unique matrix-origininating signals and cellular cross-talks plays determines their differentiation to osteoblast-like cells at the perichondral bony collar. (38,39) Furthermore, studies of chondrocyte cultures have proved that many endocrine factors exert their effect on the growth plate, at least partially, affecting the genetic expression of matrix components.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum cell death was noted at 24 hours with 50 g/ml of the antibodies, with no additional cell death after longer incubation periods. For synthetic oligonucleotide studies, preliminary time course studies (1,2,4,8,24, and 48 hours) were used to determine the time required for chondrocyte uptake of fluorescein isothiocyanate-conjugated oligonucleotides, by observation on a fluorescent microscope. From these studies, 24 hours was found to be the time required for maximal uptake.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work, we have shown that an additional survival factor, Gas-6, is produced by chondrocytes (9). Inhibition of ␤1 integrins in sternal cartilage has also been associated with apoptotic chondrocyte death (24). It is likely that several survival factors act in concert with signals from the extracellular matrix to maintain chondrocyte survival.…”
mentioning
confidence: 98%